Pemilihan Kepemimpinan Kepala Daerah Visioner Di Kota Surabaya - * Asmuriyono (DIA: Jurnal Administrasi Publik, 2013)
Local elections directly elected by the people who provide its own color pattern or against the government, especially the enactment of Act No. 32 of 2004, stated that people have the power to elect the Governor / Deputy Governor, the Regent / Deputy Regent or mayor / deputy mayor. This study aimed to analyze the characteristics of visionary local leadership and resources to analyze the function of supporting the visionary leadership elections of regional heads directly. Furthermore, the focus of this study, are as follows: (a) observed karaktetristik leadership candidate regional head / mayor in the election of local leadership in Surabaya, (b) observing the support resources that influence the selection of areas that include leadership, attitudes and behavior in support of a worthy candidate to lead the area, and (c) observing the behavior of the people in the choice of the Candidate Head of Region at the time of implementation of local elections. While the analysis of the data using descriptive qualitative approach.The first results show, for the implementation of direct elections held, the reality has yet to produce an appropriate regional head leader societal expectations, it is because regional head candidates elected not reflect the characteristics of a visionary leader. This is because local elections are no longer an effective means, there is an issue in many ways, many people believe that elections merely as a means for someone who has a particular interest to achieve their own interests, not the interests of the people again, and second, the results of research indicate that the function of supporting resources to the elected leadership is influenced by regional heads: the level of public trust, the quality of candidate the personality of the candidate and the head area. Three aspects are used as a factor for consideration in selecting candidates for regional leadership.Key Words: Head of Regional Election and Visionary Leadership